The behaviour of the smectic liquid crystall at the approach to the liquid state - Agelmenev, M.E.; Muldakhmetov, Z.M.; Bratukhin, S.M.; Polikarpov, V.V. (Publishing House of the KarSU named after E.A.Buketov, 2009)
In this work results of computer modelling of a new kind liquid crystal on the basis of derivatives of ferrocene were presented. Features of the processes proceeding in such system were studied.
Keywords: computer modelling; liquid crystal; ferrocene; molecules geometry; conformer